Achieving ultra-high strength in a face-centered-cubic FeCrCoNi high entropy alloy through dense nanotwins bundles structure prepared by cryo-rolling. (September 2022) - Zeng, Longfei; Zeng, Luming; Gao, Rui; You, Chaoping; Liu, Baixiong
Abstract: High/medium-entropy alloys (HEAs/MEAs) with simple single-phase face-centered-cubic (fcc) structures have exceptional tensile ductility and outstanding toughness, but their room-temperature strengths are moderate. Here we introduced a mixed nanostructure, composed of high density nano-scale twins in the form of bundles and nanograins in shear bands, in a single-phase fcc FeCrCoNi HEA by means of cryo-rolling at liquid nitrogen temperature (LNT), which result in a substantial enhancement of tensile strength. The as-prepared nanostructured FeCrCoNi HEA exhibits an ultra-high ultimate tensile strength of ∼1.8 GPa, an elongation-to-failure of ∼10%. The ultra-high strength originates mainly from the effective blockage of dislocation motion by the ultra-high density of internal twin and grain boundaries. The microstructural evolution and formation mechanism of the mixed nanostructure in FeCrCoNi HEA were investigated in detail by transmission electron microscopic characterization. Highlights: A mixed nanostructure, consisting of nano-grains and nanotwin bundles, was obtained through cryo-rolling. The nanostructured FeCrCoNi exhibits ultra-high yield and ultimate tensile strength of 1815 and 1864 MPa, respectively. The process used here offer an industrial approach to strengthen other FCC HEAs by generating high-density nano-scale twins.